Systematic review and meta-analysis on transplantation of ex vivo cultivated limbal epithelial stem cell on amniotic membrane in limbal stem cell deficiency - Zhao, Yuan; Ma, Lei (Cornea, 2015)
Ex vivo cultured limbal epithelial transplantation (CLET) with amniotic membrane (AM) as the substrate is a relatively new type of surgical therapy in treating limbal stem cell deficiency (LSCD). We summarize available evidence for determining the efficiency of this technique by a systematic review and meta-analysis. Searching the following electronic databases, MEDLINE, EMBASE, and the Cochrane Library, we analyzed the selected articles in 5 main aspects: donor screening, culture methods, evidence of cultivated stem cells, subjective symptoms, and adverse events through systematic review. Specifically, meta-analysis was used in evaluating improvements in ocular surface and visual acuity. A total of 18 articles involving 572 eyes of 562 patients were available. The rate of success and 2-line improvement in best-corrected visual acuity (BCVA) was 67% [95% confidence interval (CI), 0.59-0.75; I = 60%] and 62% (95% CI, 0.57-0.66; I = 37.7%), respectively; and no difference was found both in success rate [odds ratio (OR), 1.35; 95% CI, 0.63-2.89; I = 46%] and visual acuity outcome (OR, 1.53; 95% CI, 0.67-3.45; I = 42.1%) between autograft and allograft. CLET is efficacious in patients with LSCD, and no difference both in success rate and visual acuity outcome between autograft and allograft was found. Overall safety profile was good, with most side effects being transient and amenable to subsequent treatments. The long-term results of autograft and allograft will inform future treatment algorithms and techniques with random control trials and better-designed analysis.